Development of Learning Media “Wie spät ist es?” for German Speaking Skill of Language Class at SMAN 9 Malang - Aida Trieva Kirana (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This research aimed to develop a game media called Wie spät ist es?for the students from X grade language class at SMAN 9 Malang, especially in time (Uhrzeit) material. The method used in this research were the research and development method by adapting the 4D research model. The data obtained from this research are in the form of the results of filling out an open questionnaire by media experts and material experts, as well as observations from product trials. The data were analyzed qualitatively and then explained in the form of a description. Based on data analysis, it can be concluded that the game media Wie spät ist es?is feasible to be used as a support for German course for class X students.